Reconstructing Islamic Religious Education in the Era of Artificial Intelligence: A Qur’anic Framework for Ethical Digital Engagement - Abubaker Kashada; Md. Sultan Mahmud; Daniel Thompson; Liv Paulsengaard; Daniela Florina Stancu (Integrated Education Journal, 2025)
The rapid advancement of artificial intelligence (AI) has significantly transformed contemporary educational practices, including the way knowledge is accessed, interpreted, and disseminated in digital environments. These developments present both opportunities and ethical challenges, particularly for Islamic Religious Education, which seeks to guide students not only in intellectual development but also in moral responsibility. This study aims to reconstruct Islamic Religious Education in the era of artificial intelligence by developing a Qur’anic framework for ethical digital engagement. The research focuses on how key Qur’anic ethical principles such as tabayyun (verification of information), responsibility in knowledge acquisition, and ethical communication can serve as moral foundations for digital literacy and responsible technology use among students, this study employs a qualitative approach using the library research method, which involves a systematic analysis of scholarly literature related to artificial intelligence in education, digital literacy, ethics of technology, and Qur’anic perspectives on knowledge and communication. The data sources consist of peer-reviewed journal articles, academic books, and relevant research publications published within the last five to ten years. The collected literature was analyzed through content analysis and conceptual synthesis to identify key themes connecting AI-based educational environments with Qur’anic ethical teachings relevant to responsible digital engagement, the findings indicate that integrating Qur’anic ethical principles into digital learning environments provides a strong moral framework for guiding students in the responsible use of artificial intelligence technologies. Principles such as tabayyun encourage critical verification of information, while Qur’anic guidance on ethical communication promotes respectful interaction and prevents the spread of misinformation in digital spaces. The novelty of this study lies in proposing a conceptual integration between AI-driven digital learning and Qur’anic ethical epistemology, offering a framework for reconstructing Islamic Religious Education that balances technological innovation with ethical and spiritual values in the digital age